Pandemics and Income Inequality: What Do the Data Tell for the Globalization Era? - Chen, Tiejun; Gozgor, Giray; Koo, Chun Kwong (Frontiers in Public Health, 2021)
This paper empirically investigates the effects of pandemics uncertainty on income inequality. We consider a new measure of pandemics uncertainty, the World Pandemic Discussion Index (WPDI), and the post-tax (net) Gini coefficient. We focus on the panel data of 141 countries from 1996 to 2020. The results from the Feasible General Least Squares estimations indicate that the WPDI is negatively related to income inequality in 107 non-OECD countries. However, the WPDI is positively associated with income inequality in 34 OECD economies. This evidence remains robust when considering different models, including several controls, and implementing various sensitivity analyses.